Implementing Extended Producer Responsibility Legislation. (6th March 2013) - Gui, Luyi; Atasu, Atalay; Ergun, Özlem; Toktay, L. Beril
Summary The goal of this article is to contribute to the understanding of how the multiple, and sometimes conflicting, stakeholder perspectives and prevailing conditions (economic, geographic, etc.) in the implementation locality shape extended producer responsibility (EPR) "on the ground." We provide an in‐depth examination of the implementation dimension of EPR in a specific case study by examining concrete activities at the operational front of the collection and recycling system, and probing the varying stakeholder preferences that have driven a specific system to its status quo. To this end, we conduct a detailed case study of the Washington State EPR implementation for electronic waste. We provide an overview of various stakeholder perspectives and their implications for the attainment of EPR policy objectives in practice. These findings shed light on the intrinsic complexity of EPR implementation. We conclude with recommendations on how to achieve effective and efficient EPR implementation, including improving design incentives, incorporating reuse and refurbishing, expanding product scope, managing downstream material flows, and promoting operational efficiency via fair cost allocation design.